DAPL1 restrains RPE PANoptosis in experimental AMD by inhibiting GRP75-mediated mitochondria-associated endoplasmic reticulum membranes - Yan Li; Meiyu Jing; Wanxiao Wang; Wanzhen Lin; Yingxin Zhang; Tianyin Nie; Pingping Liu; Wan-ni Lu; Yu Chen; J. Fielding Hejtmancik; Qinxiang Zheng; Ling Hou; et al. (Proceedings of the National Academy of Sciences, 2026)
Retinal pigment epithelium (RPE) cell damage is a critical factor of age-related macular degeneration (AMD), the leading cause of blindness among the aged population. This study focuses on the AMD susceptible gene, Death associated protein like 1 (DAPL1), and provides insights with significant therapeutic implications. DAPL1-deficient mice exhibit dry AMD-like pathological features, a phenomenon whose mechanisms have remained largely unknown. Here, we reveal that DAPL1 deficiency promotes the formation of mitochondria-associated endoplasmic reticulum membranes (MAMs) to cause mitochondrial Ca 2+ overload and dysfunction, which triggers the activation of inflammasomes, leading RPE cells to RIPK1-mediated PANoptosis, an inflammatory programmed cell death, in an experimental dry AMD (dAMD) mouse model. Knockdown of Ripk1 in the Dapl1−/− mice RPE inhibits RPE cell PANoptosis and ameliorates the severity of dAMD pathological features. Conversely, overexpression of DAPL1 inhibits MAM formation and protects RPE cells from PANoptosis in the model. Mechanistically, DAPL1 suppresses MAM formation by downregulating GRP75 expression. This disrupts the formation of the VDAC–GRP75–IP3R axis, which comprises critical tethering proteins responsible for endoplasmic reticulum to mitochondria coupling and Ca 2+ trafficking. Knockdown of Grp75 inhibits the formation of MAM and prevents mitochondrial Ca 2+ overload, improving mitochondrial quality and inhibiting PANoptosis in RPE cells, thereby interrupting the progression of experimental dAMD in Dapl1 -deficient mice. These results unveil the role of MAMs regulated by DAPL1 in RPE cell PANoptosis and AMD progression, highlighting targeting MAM formation as a potential therapeutic strategy for treating dAMD.